High Risk Population For COVID 19 - Sheetal Sakharkar1 , Arati Raut1 ,Samrudhi Gujar1 , Savita Pohekar2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
COVID-19 is a new type of corona virus that causes the disease. ‘CO’ is for corona, VI’ for viruses, and‘D’ for illness. This disease was previously referred to as ‘2019 novel corona virus’ or ‘2019-nCoV. Coronavirus is the contagious disease (COVID-19) is arising from newly discovered. The COVID-19 virus getspeople of all ages infected. However, research to date shows that two classes of people are at greater riskof being strongly struck by COVID-19. The older people and others with existing health problems. WHOstresses that, in order to protect others, everyone must protect themselves from COVID-19. Old age peopleand individuals with underlying disabilities such as heart problems, asthma, chronic lung disease and cancerare more vulnerable to severe disease. Men is at a higher risk than females for COVID-19. ConclusionAccording to this short communication article, two groups of people are at higher risk of developing severeCOVID-19 disease. Old age people and individuals with underlying disabilities such as heart problems,asthma, chronic lung disease and cancer are more vulnerable to severe disease. These peoples have to takemore precaution to prevent covid -19 infections.